Fruit trees and domestication of animals and birds in the Nabataean Kingdom (Texas Journal of Philology, Culture and History, 2023)
Agriculture was a great source of the Nabataean economy, as evidenced by the many dams they built, the canals and sewers they built, and the water reservoirs they built, as they used very precise methods to prepare the surface of the earth to help collect rainwater that fell on nearby hills and ridges to form an appropriate amount of torrents by establishing a number of streams. Stretching from the top of the hills to the bottom and on their surface, these streams have rows of barricades made of gravel and spread in the Negev desert and are known as the Rajum of the vineyard.